A Kantian approach to education for moral sensitivity. Issue 6 (4th October 2021) - Formosa, Paul
Abstract: An important aspect of moral expertise is moral sensitivity, which is the ability to be sensitive to the presence of morally salient features in a context. This requires being able to see and acquire the morally relevant information, as well as organise and interpret it, so that you can undertake the related work of moral judgement, focus (or motivation) and action. As a distinct but interrelated component of ethical expertise, moral sensitivity can and must be trained and educated. However, despite its importance to moral education, there has been comparatively little discussion about the role of ethical sensitivity and the ways that it can be trained within the context of Kant's, and Kantian, ethics. This paper seeks to address this gap. While Kant does not explicitly focus in detail on moral sensitivity, by breaking sensitivity down into seven distinct aspects through drawing on the Four Component Model, we are able to identify a wealth of resources in Kant's work from which we can construct an account of moral sensitivity education that draws on his underlying moral theory.